COMPARATIVE CHARACTERISTICS OF IMMUNOLOGICAL RECONSTRUCTION OF WHITE MICE IMMUNIZED BY CELL WALL OF DIFFERENT SUBSPECIES OF FRANCISELLA TULARENSIS - T. P. Starovoitova; V. I. Dubrovina; S. A. Vityazeva; A. V. Korneva; T. A. Ivanova; M. Yu. Kotlov; S. V. Balakhonov (Acta Biomedica Scientifica, 2017)
At present, development of effective vaccines of new generation is an actual problem, in particular concerning the tularemia causative agent. It determines the need to search antigen determinants with high immunogenic activity. Some authors demonstrate that outer membrane proteins of Francisella tularensis possess immunological activity. This fact gave occasion to isolation and comprehensive study of F tularensis cellular envelopes as a perspective component in vaccine engineering. The influence of cell walls of F. tularensis was studied for morphological changes in immunocompetent organs of experimental animals. Cell walls were obtained from three virulence strains of living cultures: F. tularensis subsp. mediaasiatica А-61, F. tularensis subsp. nearctica В-399 A-Cole, F. tularensis subsp. holarctica 306 and vaccine strain F. tularensis subsp. holarctica 15 (extracted by Research Institute of Epidemiology and Hygiene). Cell walls of different subspecies of F. tularensis stimulate the production of antibody forming cells and cell proliferation more in T-dependent zones of lymph nodes and spleen. It has been determined that these antigen preparations do not cause stress reaction of the experimental animal organisms. Basing on the findings, we made a conclusion that there is a need for further detailed investigation of immunogenic properties of CE F. tularensis subsp. holarctica 306, F. tularensis subsp. mediasiatica А-61 and F. tularensis subsp. tularensis B-399 A-Cole as perspective components in development of tularemia vaccines.